Penerapan Project-Based Learning dalam Pembelajaran Akidah agar Dapat Menumbuhkan Akhlakul Karimah pada Mata Pelajaran PAI di SDN 021/1 Maro Sebo Ulu Kabupaten Batanghari - Sistriyanti, Sistriyanti; Marpuah, Siti; Sarinah, Sarinah (ISLAMIKA, 2025)
The purpose of this research is to examine the application of Project-Based Learning (PjBL) in the teaching of Islamic theology (Aqidah) within Islamic Religious Education (PAI) subjects at SDN 021/1 Maro Sebo Ulu. This research was conducted over three months, from September to November 2024, involving 68 teachers and all students at the elementary school. The study utilized observation, interviews, and questionnaires to collect data. PjBL was integrated directly into the Aqidah learning process, where students worked on projects designed to instill moral values. Teachers acted as facilitators, guiding students through activities that promote religious character building. Observations and interviews revealed that teachers found PjBL helpful in engaging students more actively, improving their understanding of Aqidah, and fostering positive behavioral changes. The study also conducted a classic assumption test, including normality and multicollinearity tests, to validate the regression model used. The results showed no significant multicollinearity, and the regression analysis indicated a positive and significant effect of both the PjBL strategy (X1) and teacher involvement (X2) on students' Aqidah understanding (Y). The model demonstrated a moderate correlation (R=0.540) with 29.2% of the variance in students' Aqidah scores explained by the independent variables. Additionally, the F-test confirmed the overall significance of the model. This study concludes that PjBL effectively enhances students' theoretical understanding of Aqidah and contributes to the development of good moral character in their daily lives.